The Use of Photo-Essay to Report Advances in Applied Science and Health - Macnab, Andrew John; Mukisa, Ronald; Stothers, Lynn (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2018)
Background: In the applied health and science disciples there is an expectation that project work is reported through a publication. The conventional papers written to do this follow a structure that includes sections providing background, methods, results and a discussion or conclusion, supported by figures and tables. Sometimes photographs are included, and with more on-line publications the opportunities have increased for these to be available in full color. Borrowing from the field of photojournalism photo-essays are now a publication option where a series of images are used to tell the story; these are often related to health and well-being.Aims: To summarize the methodology used to effectively combine a series of images with a brief text, and short reference list to create a visually engaging and informative short report.Guidelines: Images are taken throughout the project with consent obtained from those whose images will be recognisable. Creative licence is used to compile representative images into a sequence that conveys the background, method, results and outcome(s) of the project. Images need to be of high resolution; editing for light, colour and contrast, and cropping is allowed to increase their clarity and relevance. The ethics of photojournalism apply making inappropriate manipulation of images or erroneous captions unacceptable.Conclusions: Photo-essays are a novel and informative way to report on an applied health, social or scientific topic. The format is an excellent one to use for a brief report, or to prepare a research presentation for a scientific meeting.Keywords: Photograph, Photojournalism, Photo-manipulation.